Late nonstructural 100,000- and 33,000-dalton proteins of adenovirus type 2. II. Immunological and protein chemical analysis. - Gambke, C (1981)
For an immunological analysis of the late adenovirus type 2 nonstructural 100,000-dalton (100K) and 33K proteins, we prepared antisera against sodium dodecyl sulfate-denatured, gel-purified 100K and 33K proteins. These antisera were tested for potential cross-reactivity, since according to a previous report (Axelrod, Virology 87:366--383, 1978) these two proteins exhibit extensive amino acid homologies. However, immunoprecipitations of 100K and 33K proteins, as well as a sensitive immune replica technique, did not reveal any immunological relationship between these proteins. Therefore, using fingerprint peptide analysis, we investigated the structural relationship between 100K and 33K proteins labeled with a 14C-amino acid mixture or with [14C]proline after digestion with trypsin. We detected only minor, if any, amino acid homologies, indicating that the 100K and 33K proteins are not structurally related.